Empowering Sustainable Village Tourism in Payangan Jember Through Lautify and the Blue Economy - Siti Nur Ameilia Rahmawati; Siska Aprilia Oktaviani; Adelia Eka Puspita Ansori; Aulya Mardina; Oryza Ardhiarisca; Rahma Rina Wijayanti (Journal of Science and Research, 2025)
The era of the Industrial Revolution 4.0 and Society 5.0 has positioned digitalization as a key strategy to enhance business competitiveness in the post-COVID-19 period. Digital transformation opens new opportunities for the maritime sector, which holds significant potential yet remains underutilized. This study examines the integration of the Blue Economy concept and digitalization in the development of coastal MSMEs in Payangan Beach, Jember Regency, as an effort to sustainably improve community welfare. The utilization of marine resources in the area is still limited to raw forms, which have low economic value. Processing marine products into value-added items such as fish floss, fish skin crackers, and fish meal is considered effective in boosting the local economy. Digital marketing through social media and online marketplaces is employed to expand market reach. The implementation of this initiative includes training in product processing, financial management, and digital marketing for housewives and youth in Sumberejo Village. The Blue Economy concept is applied by emphasizing environmental sustainability and waste reduction. The results of the study indicate that integrating digitalization and the blue economy holds the potential to create new economic opportunities and strengthen the foundation for sustainable development in coastal areas.